Event-triggered output feedback H∞ control for networked Markovian jump systems with quantizations. (May 2017) - Zha, Lijuan; Fang, Jian-an; Li, Xiaofan; Liu, Jinliang
Abstract: This paper is concerned with H ∞ output feedback control of event-triggered Markovian jump systems with measured output quantizations. An event-triggered mechanism and a quantization scheme are designed to reduce the occupancy of the limited network resources. The measured output is directly transmitted to the event generator, whether the released signal can be sent out to the controller through the quantizer depends on the triggering condition. A new Markovian jump time-delay system model with external disturbances is then presented and sufficient conditions are derived to guarantee the stability of the resulting closed-loop system and prescribed performance. Criteria for co-designing both the output feedback gain and the trigger parameters are established. Finally, a numerical example confirms the effectiveness of the proposed method.